Development and Evaluation of Lapatinib Solid Lipid Nanoparticles in the Management of Breast Cancer (International Journal of Pharmaceutical Sciences and Drug Research, 2019)
The current research was aimed at formulation of Lapatinib loaded solid lipid nanoparticles (SLNs) followed by evaluation for effective treatment of breast cancer. The formulations prepared by homogenization and ultrasonication and evaluated for zeta potential, particle size, polydispersity index, entrapment efficiency and in-vitro dissolution studies. Entrapment efficiency studies indicated proportional relation between concentration of lipid and the amount of drug entrapped. The physicochemical parameter evaluation data indicated 94.27% entrapment efficiency, 130 nm particle size and -19.9 zeta potential for stable formulation. The in vitro drug dissolution studies indicated that Lapatinib loaded SLNs (F6) formulated with Dynasan 116 and Egg Lecithin was suitable for anti-cancer therapy with higher drug dissolution rate.